Involvement of circulating microRNAs in the pathogenesis of atherosclerosis in young patients with obesity - Mažgútová, Nikoleta; Witvrouwen, I; Czippelova, B; Turianikova, Z; Cernanova Krohova, J; Kosutova, P; Kuricova, M; Cierny, D; Mikolka, P; Van Craenenbroeck, E; Javorka, M (Physiological research, 2024)
Obesity is considered an important factor contributing to the development of atherosclerosis. Inflammation plays a key role in endothelial dysfunction (ED), an initial stage of the atherosclerotic process. Several microRNAs (miRNAs) may play an important role in the inflammatory process, but there is a lack of information about their participation in the early stages of atherosclerosis development in patients with obesity. We aimed to assess the relations between plasma concentration of selected miRNAs, ED evaluated by reactive hyperemia index (RHI), inflammatory markers and other factors involved in the pathogenesis of atherosclerosis in adolescents and young adults with obesity. Participants (30 males, 30 females; aged 15 25 years) were divided into two groups: those with overweight/obesity (OW/O) (20 males, 20 females) and controls (C) (10 males, 10 females). The plasma concentrations of inflammatory markers, cytokines, adipocytokines, markers of lipid profile and glucose metabolism and selected miRNAs (miR 92, 126, -146a, -155) were analyzed. No significant differences in any of the miRNAs were found between the groups. MiR-146a correlated positively with RHI. Dividing the group by sex showed more significant associations between miRNA and analyzed parameters (IL-6, fasting glycemia) in men. Several observed correlations indicate a potential role of miRNAs in inflammation, the atherosclerotic process and glycemic control, primarily in male subjects with obesity. The relatively low number of observed associations between assessed parameters related to obesity and the pathogenesis of its complications could be attributed to the early stage of the atherosclerotic process in young subjects with obesity, where only subtle abnormalities are expectedly found. Key words Endothelial dysfunction, Atherosclerosis, Obesity, MicroRNA, Reactive hyperemia index.
Keywords: obezita; cirkulující mikroRNA; Humans; Circulating MicroRNA; Female; mladý dospělý; dospělí; ateroskleróza; lidé; Biomarkers; Adult; ženské pohlaví; biologické markery; Male; Atherosclerosis; Adolescent; Young Adult; Obesity; mužské pohlaví; mladiství